West Indies Cricket Team, England, 1963 - (:unkn) unknown (My University, 2022)
A photograph of the West Indies Cricket Team that toured England in 1963. Taken in front of Lord's Pavilion. At the back: HNP £50 1963. COPYRIGHT PHOTO ISSUED BY CENTRAL PRESS PHOTO LTD, 6& 7, GOUGH SQUARE, FLEET STREET, LONDON, E.O.4. FLEET STREET 2266/7
Landscape ; Black and white ; 10 x 8 inches
Keywords: Historic Buildings; Cricket Players; Cricket; Sports; Cricketers; West Indies Cricket Team; Lord's Cricket Ground